SUSTAINABLE MANAGEMENT OF RED SPIDER MITE (TETRANYCHUS SP.) INFESTING EGGPLANT (SOLANUM MELONGENA L.) AT FIELD LEVEL - GHOSH, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The eggplant crop is susceptible to various insect and mite pests of which red spider mite, To•anychus sp. (Tetranychidae : Acarina) is most predominant. Control of this pest by using chemical insecticides could lead to human health hazards arising from toxic residues in the fruit. One botanical insecticide azadirachtin (Neemactin 0.15 EC) @ 2.5 ml/L, and four botanical extracts, tobacco (Niciliana tahacum) leaf extract @ 10.0%, Polygonum hydropiper floral part extract a, 10.0%. Pongamia pinnata fruit extracts@ 10.0%, and Spilanthes paniculata floral parts extract@ 5.0%, and one treatment containing mixture of azadirachtin and propergite (@ 2.5 ml + 1.5 ml/L were evaluated and compared with the ability of propergite (Omite 57 EC), a chemical insecticide rib, 3m I/ L to control the mite pest, Tetranychus sp.. Propergite treatment resulted in the best suppression of mite population (88.55% suppression), closely followed by mixed formulation of botanical pesticide, azadirachtin and chemical pesticide, propergite (85.55% suppression). However among the bio-pesticides including plant extracts Polygonum flower extract (at 10% concentration) was the most effective providing moderate to higher control (51.04% suppression). Azadirachtin individually did not produce good results (moderate mite suppression) but when used as a mixture with lower dose (1.5 ml/L) of chemical insecticide, propergite provided better results recording more than 85 % suppression.